Outcomes of Laproscopic Hysterectomies: An assessment of a learning curve experience of a Gynae laparoscopic surgeries: Assessment of a Learning Curve Experience of Gynae Laparoscopic Surgeries - Fatima, Mahwish; Maqsood, Sadaf; Laqa, Sarwat; Kashif, Samra; Rehman, Sana; Masood, Zubaida (Pakistan Journal of Health Sciences, 2022)
Among the most frequent gynecological operations conducted is the hysterectomy. Objective: To determine the outcome of TLH in benign uterine pathology of up to 12-week size uterus. Methods: It was a prospective case series carried out at Obstetrics and Gynecology department of Memon medical institute hospital, Karachi from January 2019 to January 2021. All patients who underwent laparoscopic hysterectomy secondary to benign utero- ovarian pathology were consecutively enrolled. Demographic characteristics of the patients along with the presence of co-morbidities, hospital admission details, surgical procedure and intra and post-operative complications were noted. The surgery performed with similar technique in all cases. If patients were deemed to be fit for release after 48 hours following surgery, they were discharged. The postoperative follow-ups were performed at 10th, 30th, and 3 months. Results: Of 50 patients, the mean age was 50.5 years. The main indication of hysterectomy is adenomyosis diagnosed in 20 patients. There were 4 laparoscopic assisted vaginal hysterectomies and 46 were total laparoscopic hysterectomies. History of previous laparotomies was observed in 12, previous cesarean and bilateral tubal ligation in 6 each, history of mesh repair of umbilical hernia in 4 while history of VP shunt was observed in 2 patients. Eight patients converted into laparotomy due to technical difficulty in controlling hemorrhage of uterine artery. Total rate of intra and post-operative complications was 40%. Conclusion: Laparoscopic approach for hysterectomy is a safe alternative to conventional hysterectomy for benign uterine pathology of up to 12 weeks size uterus.